The Effect of Cold Compress on Pain Intensity in Fractured Patients - Lubis, Citra Amelia; Tanjung, Dudut; Asrizal, Asrizal (Jurnal Keperawatan Soedirman, 2021)
Fracture occurs due to the damage of the shape and function of the bone, and the fractured patients generally experience pain. One of the interventions to reduce pain intensity in fracture patients is cold compress. This study aims to identify the effectiveness of cold compress on pain intensity in fracture patients in H. Adam Malik Hospital Medan. This is a quantitative study with a quasi-experimental design approach with an equivalent control group pretest-posttest design. The number of samples is 70 respondents consisting of 35 people for each intervention and control group, respectively, which was collated by consecutive sampling. Data analysis used paired t-test and independent t-test. The results showed that there was a significant influence before and after cold compress intervention on pain intensity (p value 0.001 (p = <0.05)). There is a significant difference between the intervention with cold compresses and the hospital standard intervention on pain intensity in fracture patients (p value 0.001 (p = <0.05)). It can be concluded that cold compress has a significant effect on the pain intensity in fracture patients. Cold compress is one of the nursing interventions that can help to reduce the intensity of fracture pain.